2011
DOI: 10.1086/662039
|View full text |Cite
|
Sign up to set email alerts
|

Years, Months, and Days versus 1, 12, and 365: The Influence of Units versus Numbers

Abstract: Quantitative changes may be conveyed to consumers using small units (e.g., change in delivery time from 7 to 21 days) or large units (1–3 weeks). Numerosity research suggests that changes are magnified by small (vs. large) units because a change from 7 to 21 (vs. 1–3) seems larger. We introduce a reverse effect that we term unitosity: changes are magnified by large (vs. small) units because a change of weeks (vs. days) seems larger. We show that numerosity reverses to unitosity when relative salience shifts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 52 publications
5
82
4
Order By: Relevance
“…In other words, the purchase quantity becomes more influential when the discount is based on dollars. This conclusion is consistent with previous findings on the unit effect, showing that the unit in which quantitative information is described affects consumer perceptions and decisions (Burson et al, 2009;Monga and Bagchi, 2012;Pandelaere et al, 2011).…”
Section: Discussion and Managerial Implicationssupporting
confidence: 93%
“…In other words, the purchase quantity becomes more influential when the discount is based on dollars. This conclusion is consistent with previous findings on the unit effect, showing that the unit in which quantitative information is described affects consumer perceptions and decisions (Burson et al, 2009;Monga and Bagchi, 2012;Pandelaere et al, 2011).…”
Section: Discussion and Managerial Implicationssupporting
confidence: 93%
“…If the effects emerge in nonnumerical contexts then it would rule this out. This study also rules out a numerosity-based explanation (e.g., Bagchi and Li 2011;Bagchi and Davis 2012;Monga and Bagchi 2012;Pelham, Sumarta, and Myaskovsky 1994) for our effects-that is, our effects emanate not because of directionality, as we propose, but because of the largeness of numbers.…”
Section: Discussioncontrasting
confidence: 43%
“…The results are inconclusive. Monga and Bagchi (; Study 2) observed that the numerosity effect does indeed emerge in an intertemporal choice context, but only for concrete, not for abstract, mindsets. Moreover, their study does not tell us what the default numerosity effect may be, because the study lacks a control condition (i.e., when no mindset is induced).…”
Section: The Numerosity Heuristicmentioning
confidence: 96%